1995
DOI: 10.1007/bf00164890
|View full text |Cite
|
Sign up to set email alerts
|

Inter-root movement of Azospirillum brasilense and subsequent root colonization of crop and weed seedlings growing in soil

Abstract: Inter-root movement and dispersion of the beneficial bacterium Azospirillum brasilense were monitored in root systems of wheat seedlings growing in the field and in growth chamber soil trays. Two strains were used, a motile wild-type strain (Cd, mot(+)) and a motility deficient strain (mot(-)), which was derived from the Cd strain. Root colonization by two wild-type strains (Cd and Sp-245) was studied in 64 plant species growing in pots in the greenhouse. The two wild-type strains of A. brasilense were capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…The role of motility by PGPR Pseudomonas fluorescens and Bacillus sp. has been demonstrated in previous studies (Misaghi et al, 1992; Bashan and Holguin, 1995; Lugtenberg and Kamilova, 2009). Moreover, recovery of bacterial colonies from inoculated plants showed that HSW-16 was efficient to colonize plants (Anith, 2009; Joshi and Bhatt, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…The role of motility by PGPR Pseudomonas fluorescens and Bacillus sp. has been demonstrated in previous studies (Misaghi et al, 1992; Bashan and Holguin, 1995; Lugtenberg and Kamilova, 2009). Moreover, recovery of bacterial colonies from inoculated plants showed that HSW-16 was efficient to colonize plants (Anith, 2009; Joshi and Bhatt, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…As demonstrated in this study, Azospirillum appears to bind to mangrove roots in a similar manner. Species of Azospirillum have been reported to colonize the roots of a wide variety of plant species [19,27,50]. This study extends the range of host plants for this genus to one species of marine mangroves.…”
Section: Resultsmentioning
confidence: 71%
“…Root colonization in situ by Azospirillum spp. required live bacteria [4], was governed by bacterial motility in the soil, and was stimulated by plant exudates [4][5][6][7].…”
mentioning
confidence: 99%